2014
DOI: 10.1080/0969594x.2014.944086
|View full text |Cite
|
Sign up to set email alerts
|

The promise and reality of formative assessment practice in a continuous assessment scheme: the case of Trinidad and Tobago

Abstract: Continuous Assessment (CA) systems are externally directed, curriculum-based assessment schemes used for both summative and formative purposes within classrooms. CA has been implemented as national policy in several postcolonial developing countries and is believed to hold great promise for improving education outcomes. This theory-driven evaluation (TDE) used a mixed methods research design to interrogate the nature of CA practice. The focus was on stakeholders' understanding and practice of formative assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…However, studies on random samples of teachers have found limited extent and fidelity in teachers' implementation of professional development programmes focusing this approach to formative assessment, and consequently no impact from the programme on student achievement (Bell, Steinberg, Wiliam, & Wylie, 2008;Randel et al, 2011). In general, attempts to promote formative assessment have frequently been unsuccessful in accomplishing a substantially developed formative assessment practice (Carless, 2005;De Lisle, 2015;Hume & Coll, 2009;James & McCormick, 2009;Marshall & Drummond, 2006;Schneider & Randel, 2010;Wylie & Lyon, 2015), to the extent that increased student achievement was obtained (Bell et al, 2008;Carless, 2005;Jönsson, Lundahl, & Holmgren, 2015;Randel et al, 2011;Schneider & Randel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on random samples of teachers have found limited extent and fidelity in teachers' implementation of professional development programmes focusing this approach to formative assessment, and consequently no impact from the programme on student achievement (Bell, Steinberg, Wiliam, & Wylie, 2008;Randel et al, 2011). In general, attempts to promote formative assessment have frequently been unsuccessful in accomplishing a substantially developed formative assessment practice (Carless, 2005;De Lisle, 2015;Hume & Coll, 2009;James & McCormick, 2009;Marshall & Drummond, 2006;Schneider & Randel, 2010;Wylie & Lyon, 2015), to the extent that increased student achievement was obtained (Bell et al, 2008;Carless, 2005;Jönsson, Lundahl, & Holmgren, 2015;Randel et al, 2011;Schneider & Randel, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The practice of continuous assessment is reported world-wide (Ramon-Muñoz, 2015;Bjaelde et al, 2017). Continuous assessment is also supported by conventions (e.g., the European Higher Education Area) (de la O González et al, 2015), national legislation (De Lisle, 2015), quality promoting bodies, and institutional policies (Muskin, 2017).…”
Section: Continuous Assessmentmentioning
confidence: 99%
“…A growing body of literature emphasize Continuous Assessment (CA), which in this manuscript refers to online continuous assessment as well, as a sound assessment strategy in higher education. CA helps reduce the negative effects of highstakes once-off examinations (rote memorization, cramming, and high anxiety) and helps to promote student learning (De Lisle, 2015;Holmes, 2018). The application of CA in higher education spans different disciplines (Rezigalla et al, 2017;Day et al, 2018c;Nayak et al, 2020;Zhan, 2020) and various pedagogic approaches (Day et al, 2018b;Llamas-Nistal et al, 2019;Chong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Summative assessments were traditionally limited to examination venues (venue-based) and take place at the end of the tuition period as the final examination or evaluation, to determine whether the outcomes of a module have been successfully achieved (Chaudhary and Dey 2013;Dunn and Mulvenon 2009; South African Qualifications Authority [SAQA] 2014). If there is a high alignment between formative and summative assessments, continuous assessments can be successfully integrated or combined (De Lisle 2015). Both formative and summative assessments can be in the form of online non-venue-based technology-enhanced assessments.…”
Section: Literature Reviewmentioning
confidence: 99%